Measurement of Phenolic Compounds by Spectrometry and Chromatography in Lime Juices - Fatemeh Shakeri; Mohammad Shakeri; Fatemeh Pour Ramezani; Mohadeseh Pirhadi; Masoud Aman Mohammadi; Samira Shokri; Tayebeh Zeinali (Journal of Spectroscopy)
Juice demand has been increasing at a rapid rate in recent years, and one of the major efforts underway to meet this demand is to minimize changes during the juice process. Due to the high consumption of juice and the carcinogenicity of synthetic and chemical substances, this research uses high performance liquid chromatography (HPLC) and spectrophotometry to detect fake juices. For the detection of fraud, the tests of sodium and potassium content along with determining the amount of flavonoids (hesperidin and eriocitrin) were carried out using spectrophotometry and HPLC. The results showed the average amount of total polyphenol was from 32.4 to 42.6 mg L-1. The total polyphenol content in all samples conformed to the standard, and there was no significant difference between the samples and the standard. The amounts of flavonoids (hesperidin and eriocitrin) in the juice samples were below the standard level (a minimum of 90 and 20 g/mL, respectively). Also, there was a significant difference between the mean sodium and potassium content of standard versus feigned juices. Generally, the amount of hesperidin, eriocitrin, Na+, and K+ as diagnostic biomarkers of natural juice in all samples was below the standard level. All the analysed samples in the experiment were nonstandard. There is a lot of fraud in the juice business, so it has been suggested that the government should have more control over how manufacturing companies make juice.